Supporting integrative maritime spatial planning by operationalising SEANERGY – a tool to study cross-sectoral synergies and conflicts - Ida Maria Bonnevie; Henning Sten Hansen; Lise Schrøder (International Journal of Digital Earth, 2021)
With growing pressures on marine ecosystems and on marine space, an increasingly needed strategy to optimise the use of marine space is to co-locate synergic marine human uses in close spatial–temporal proximity while separating conflicting marine human uses. The ArcMap toolbox SEANERGY is a new, cross-sectoral spatial decision support tool (DST) that enables maritime spatial planners to consider synergies and conflicts between marine uses to support assessments of co-location options. Cross-sectoral approaches are important to reach more integrative maritime spatial planning (MSP) processes. As this article demonstrates through a Baltic Sea analysis, SEANERGY presents a cross-sectoral use catalogue for MSP through enabling the tool users to answer important specific questions to spatially and/or numerically weight potential synergies/conflicts between marine uses. The article discusses to what degree such a cross-sectoral perspective can support integrative MSP processes. While MSP integrative challenges still exist, SEANERGY enables MSP processes to move towards developing shared goals and initiate discussions built on best available knowledge regarding potential use-use synergies and use-use conflicts for whole sea basins at once.